Inadequate management of hyperlipidaemia after coronary bypass surgery shown by medical audit. Issue 5 (November 1994) - Northridge, D B; Shandall, A; Rees, A; Buchalter, M B
Abstract : OBJECTIVE–To audit the detection and management of hyperlipidaemia in patients who have had coronary bypass surgery. PATIENTS–100 consecutive patients (81 men), mean age 61, who had survived at least 3 months after coronary bypass surgery. METHODS–Retrospective review of case notes and computerised biochemistry records. RESULTS–83 patients had at least one lipid measurement in the hospital, and of the remaining 17 patients, 10 had undergone urgent or emergency surgery. The median (range) total cholesterol was 6.7 (4.0-11.7) mmol/l and the triglyceride concentration was 2.1 (0.6-18.4) mmol/l. Only 30 patients were referred to a dietician, and 12 were given a lipid lowering drug–these interventions were no more frequent in patients with a cholesterol concentration above than below the median. CONCLUSIONS–Although a high proportion of patients who undergo routine coronary bypass surgery have their plasma lipid concentrations measured, many patients with raised cholesterol concentrations, who would benefit from lipid lowering interventions, are not offered them.